The phenomenon of free inter-mingling among students of opposite sex at IIUM : a juristic evaluation - Nurul Izzah binti Yahaya (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
Islamic law as an all- embracing code of human behavior of human life, social and personal. In this context, it imposes certain rules when it comes to social encounter between the members of opposite sex in the course of day today social interaction. However, this Islamic principle seems not to have been properly grasped by many youngsters in our time. Even at IIUM some male and female students at IIUM involve themselves in free intermingling which according to Students' Discipline Rules 2004 (Amendment 2006) of the university cannot be classified as legitimate social encounters. Accordingly, the researcher concerned herself with this question and conducted a survey among IIUM students. The finding of this study which involved 200 students from various Kulliyyah seems to confirm this assertion. The reasons leading to such a phenomenon include: first, lack of proper Islamic moral upbringing in the family; second, weak law enforcement at IIUM and lastly lack of overall reinforcement of good values in class and IIUM environment. Consequently, people at all these levels have a moral duty to internalize the law of haram and halal in social interaction among members of the opposite sex if we want to build a wholesome ummah.